2014
DOI: 10.1161/strokeaha.113.003038
|View full text |Cite
|
Sign up to set email alerts
|

Extending the Indications of Flow Diversion to Small, Unruptured, Saccular Aneurysms of the Anterior Circulation

Abstract: The University Institutional Review Board approved the study protocol. Forty consecutive patients with unruptured, previously untreated, small (<10 mm) aneurysms treated with PED (2011PED ( -2013 at our institution were identified from a prospectively maintained database. Patients treated with PED and adjunctive coiling were not included in the analysis. Every patient treated with the PED was matched to 4 control patients treated with stent-assisted coiling (2004-2011) based on patient age, sex, aneurysm locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
93
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(97 citation statements)
references
References 38 publications
1
93
0
3
Order By: Relevance
“…Улучшения касаются как анатомических результатов полной окклюзии ЦА при повторных ангиограммах, так и показателей трав-матичности и летальности при операциях [38]. Общее количество интраоперационных осложнений эндова-скулярного койлинга находится на уровне 3,7-5,3%, интраоперационной смертности -1,1-1,5% [39], что соответствует показателям открытой операции -4-11 и 1-3%, соответственно.…”
Section: Discussionunclassified
“…Улучшения касаются как анатомических результатов полной окклюзии ЦА при повторных ангиограммах, так и показателей трав-матичности и летальности при операциях [38]. Общее количество интраоперационных осложнений эндова-скулярного койлинга находится на уровне 3,7-5,3%, интраоперационной смертности -1,1-1,5% [39], что соответствует показателям открытой операции -4-11 и 1-3%, соответственно.…”
Section: Discussionunclassified
“…5,9,10,16 The latter approach has been increasingly used to treat large and giant aneurysms of the internal carotid artery, and recent studies have shown flow diverters to have a safety profile comparable to that of traditional endovascular techniques. 9,10,16 Limitations This study is limited by its retrospective design. Many aneurysms treated with coil therapy during the study period were not included in the analysis because the patients did not have available short-term and longterm follow-up DSA images.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of complete occlusion in the FD group with at least 6 months of follow-up of 64.4% is lower than that in other flow-diverter studies; however, the low rate of retreatment (6%) is in line with those previously reported. [24][25][26][27][28] In the Pipeline for Uncoilable or Failed Aneurysms Study, 24 the rate of complete occlusion was 82% at 6 months and 86% at 12 months. Likewise, in a large single-center consecutive series of 54 patients, Lylyk et al 25 found high rates of completeaneurysm occlusion of 93% and 96% at 6 and 12 months, respectively.…”
Section: Angiographic Outcomesmentioning
confidence: 99%